Voice, silence, and self : negotiations of Buraku identity in contemporary Japan - Bondy, Christopher, 1969- (Harvard East Asian monographs, 2015)
"Based on extensive ethnographic research and interviews, this longitudinal work explores the experience of Burakumin youth from two different communities and with different social movement organizations"--